Contribution to the development of Ecuador’s Audiovisual Translation Industry through an analysis of Subtitling Standards based on the translation of a movie script abstract of “The Great Gatsby". - Ramírez Guzmán, Claudia Milena (2016)
This research work aims to provide a number of standardized steps for subtitling to contribute as a reference to the existing subtitling industry that lacks this type of material. Among these steps are: transcript of the dialogue, translation, time on screen, simulation and correction. The first step is crucial when starting to subtitle audiovisual material, since the written part is needed in order to proceed with the second step, which is the translation itself. The latter encompasses the techniques the translator decides to apply to render the work. The last steps comprise the simulation and the correction, in which the final result is trialed so as to check if corrections are needed or demanded by the client. Furthermore this research confirmed the interest of the target group in learning professionally this process and their discontent with the current foreign subtitling.